2021
DOI: 10.1155/2021/5313832
|View full text |Cite
|
Sign up to set email alerts
|

Viral Coinfection among COVID-19 Patient Groups: An Update Systematic Review and Meta-Analysis

Abstract: Background. Coinfections have a potential role in increased morbidity and mortality rates during pandemics. Our investigation is aimed at evaluating the viral coinfection prevalence in COVID-19 patients. Methods. We systematically searched scientific databases, including Medline, Scopus, WOS, and Embase, from December 1, 2019, to December 30, 2020. Preprint servers such as medRxiv were also scanned to find other related preprint papers. All types of studies evaluating the viral coinfection prevalence in COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 79 publications
1
38
0
1
Order By: Relevance
“…These data highlight the importance of COVID-19 vaccination for those aged ≥5 years and other prevention strategies to protect children and adolescents from COVID-19, particularly those with obesity and other underlying health conditions. Further research and surveillance for viral coinfections with SARS-CoV-2 in pediatric patients can inform public health and capacity planning (10).…”
Section: Discussionmentioning
confidence: 99%
“…These data highlight the importance of COVID-19 vaccination for those aged ≥5 years and other prevention strategies to protect children and adolescents from COVID-19, particularly those with obesity and other underlying health conditions. Further research and surveillance for viral coinfections with SARS-CoV-2 in pediatric patients can inform public health and capacity planning (10).…”
Section: Discussionmentioning
confidence: 99%
“…It is also vital to detect SARS‐CoV‐2 as early as possible since SARS‐CoV‐2 may be coinfected with other microbial pathogens. 2 Infection with SARS‐CoV‐2 may alter the human's microbiota, which further may affect the immune system. 3 Based on a systematic review, 4 a high prevalence of pathogenic microorganism was found among COVID‐19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of SARS‐CoV‐2 is the first step in assessing cases. It is also vital to detect SARS‐CoV‐2 as early as possible since SARS‐CoV‐2 may be coinfected with other microbial pathogens 2 . Infection with SARS‐CoV‐2 may alter the human's microbiota, which further may affect the immune system 3 .…”
Section: Introductionmentioning
confidence: 99%
“… 3 Mass testing against SARS‐CoV‐2 and in some circumstances alone with other bacterial, viral, or fungal microbiota is also encouraged for a wide range of COVID‐19 control measures, such as screening for community transmission 4 and evaluation for disease progression of COVID‐19 patients with/without coinfection of other microbial agents. 5 , 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%